Donor-acceptor-based two-dimensional polymer as a supercapacitor electrode with long cycling stability - Bhagyasree, T. M.; Puthiyaveetil, Priyanka Pandinhare; Kumar, Viksit; Asokan, Kiran; Sreekumar, K.; Babu, Sukumaran Santhosh (New Journal of Chemistry, 2023)
The high demand for energy and energy-storage devices urged organic 2D polymers as a potential candidate in this area. One of the major attractions of 2D polymers in electrochemical applications is their long cycling stability due to their rigid and porous structure. Herein, we developed a 2D polymer comprised of donor-acceptor units exhibiting reasonably good performance as a supercapacitor. The 2D polymer displayed a maximum specific capacitance of 218 F g-1 at a current rate of 0.1 A g-1, a higher power density of 4648.35 W kg-1, and an energy density of 7.05 W h kg-1. In a cycling stability test, it demonstrated a capacitance retention of 70% over 10 000 continuous charge-discharge cycles at a current rate of 2.5 A g-1. Such long cycling stability was attributed to the donor-acceptor units and the crystalline nature of the polymer. The sensible selection of the building blocks of the 2D polymers is crucial for the performance and hence provides scope for improvement. An organic donor-acceptor-based 2D polymer, a promising candidate for energy storage devices, displays a specific capacitance of 218 F g-1, a power density of 4648.35 W kg-1, an energy density of 7.05 W h kg-1, and a capacitance retention of 70% over 10 000 cycles.

Diamondoid all-carbon porous aromatic framework host for lithium-sulfur batteries - Kumar, Viksit; Javaregowda, Bharathkumar H.; Devasia, George; Narayanan, Aswini; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Babu, Sukumaran Santhosh (Small, 2025)
Lithium-sulfur batteries (LSBs) hold incredible potential as next-generation energy storage systems. However, practical applications of LSBs are significantly hindered by several critical challenges. For the first time, scalable all-carbon porous 3D polymers (3DPs) that do not contain heteroatoms or functional groups and do not require post-functionalization are investigated as hosts in lithium-sulfur batteries, demonstrating enhanced cycling stability and overall battery performance. The pyrene-containing 3DP exhibits 75% capacity retention after 600 cycles at 1 C and 52% capacity retention after 1300 cycles at 0.2 C, better than phenyl comprising 3DP. Furthermore, even at higher sulfur loading (4.1 mg cm(-2)) with an electrolyte/sulfur ratio of 5 mu L mg(-1), pyrene 3DP displayed a high capacity of 600 mA h g(-1) and stable performance over 250 cycles with negligible capacity fade. The defined pore structure of 3DPs prevents the migration of polysulfides through physical confinement and the large pi -clouds of 3DPs interact with the negative charge-bearing polysulfides generated in charge-discharge cycles through anion-pi interaction. In this way, The design ensures that the host 3DPs interact with neutral sulfur and anionic polysulfides, resulting in an excellent performance.
Keywords: 3D polymers; Batteries; Li-Sulfur battery; porous materials; pyrene